Analisis Tingkat Kepuasan Anggota Terhadap Pelayanan pada Koperasi Serba Usaha Bintang Muda 88 - Yanta Sry Paerong; Isak Pasulu; Abedneigo C. Rambulangi (CV. Ulil Albab Corp, 2024)
This research aims to examine and evaluate the level of member satisfaction with services at the Bintang Muda 88 cooperative enterprises. The need for further development in member satisfaction towards services at Bintang Muda 88 cooperative enterprises serves as the basis for the author's research. This study utilized a quantitative descriptive research method. The research was conducted at Bintang Muda 88 Cooperative Enterprises located in the Se’pon sub-district, Lapandan Village, Makale District, Tana Toraja Regency, South Sulawesi Province. Data collection was carried out using a questionnaire method among members of Bintang Muda 88 Cooperative Enterprises who were applying for credit from January to May 2024 at the Makale branch office. The research findings indicate that based on the survey measurement results of member satisfaction with services at Bintang Muda 88 Cooperative Enterprises at the Makale branch office, the category is deemed good, with a weighted average score of 3.16 or IKM conversion of 78.20.